Dielectric properties of dried vegetable powders and their temperature profile during radio frequency heating. (January 2016) - Ozturk, Samet; Kong, Fanbin; Trabelsi, Samir; Singh, Rakesh K.
Abstract: Dielectric properties of selected vegetables powders as influenced by moisture content (MC), compaction density and temperature were determined using a precision LCR meter and liquid test fixture at radio frequency (RF) ranging from 1 to 30 MHz. The RF heating rate of samples was evaluated using a 27.12-MHz, 6-kW RF oven. The results showed that dielectric properties, namely, the dielectric constant, ε ′, and loss factor, ε ′′, of vegetable powders were influenced by MC, compaction density and temperature of the samples and the RF frequency. Both the dielectric constant and loss factor increased with increasing MC and temperature, but decreased with increasing frequency. Additionally, dielectric properties of samples increased with compaction density to a peak, then decreased. The relationship between MC, temperature and dielectric properties of broccoli powder at 13.56 and 27.12 MHz can be described by quadratic models with high correlation coefficients (R 2  > 0.96). The RF heating rate in samples increased linearly with dielectric loss factor and MC. The information provided in this study is useful to develop an effective RF heating strategy to pasteurize dried vegetable powders. Highlights: Dielectric properties were tested for selected vegetable powders. Effect of compaction density, moisture and temperature was studied. Heating rate of vegetable powders during RF heating were investigated. Regression equations were derived to predict ε′ and ε″ of broccoli powder.